Pemberdayaan mitra desa dalam pencegahan pernikahan usia dini: pendampingan kader dan orang tua melalui pembentukan kegiatan pelayanan kesehatan remaja (KPKR) di Desa Bukit Raya - Urnia, Ega Ersya; Suryani, Heni; Cybronika, Luthi Metta Medina (Jurnal PADE: Pengabdian & Edukasi, 2024)
Bukit Raya Village recorded 34 teenagers who married at an early age. The number of contributions and roles of partners and target partners in this PKM scheme community service is village partners through community groups who contribute as a role model for the sustainability of community service activities in villages that participate in training and mentoring on the prevention of Early Marriage with the formation of Youth Health Service Activities (KPKR). The target indicators of community service achievement are to form an Adolescent Health Service Activity Team (KPKR) to improve the knowledge and skills of health cadres in providing education to the community, increase the knowledge and skills of target partners about providing education to the community about early marriage to 100%, help increase the achievement of reproductive health discovery and services according to standards from 66.0% to 77.0% and improve the skills of village community groups and cadres as mentors and role models in providing education to the community about early marriage from 0% to 100%.